AB0132 Intra-articular glucocorticoid injections decrease the number of steroid hormone receptor positive cells in synovial tissue of patients with persistent knee arthritis. (23rd January 2014) - van der Goes, M.C.; Straub, R.H.; Wenting-Van Wijk, M.J.; Capellino, S.; Jacobs, J.W.; Jahangier, Z.N.; Rauch, L.; Bijlsma, J.W.; Lafeber, F.P.
Abstract : Objectives: To explore changes in numbers of steroid hormone receptor positive cells in synovial tissue (ST) after intra-articular glucocorticoid injection, to correlate these changes to changes in clinical parameters, and to evaluate whether the number of steroid hormone receptor positive cells predicted the clinical response to the glucocorticoid injection. Methods: Fourteen patients with persisting knee arthritis despite at least two previous injections in an outpatient setting received an intra-articular injection with glucocorticoids, followed by three days of admission with bed rest. Clinical efficacy was assessed at six and twelve weeks. ST biopsies were taken two weeks before and twelve weeks after injection. Presence of different cell types (T cells, macrophages, fibroblast-like synoviocytes) and numbers of glucocorticoid-, androgen-, and estrogen alpha and beta receptor positive cells were evaluated by histochemistry. Results: Patients showed, despite previous failing, good clinical response to glucocorticoid injection with significant improvement in erythrocyte sedimentation rate, visual analogue scale (VAS) for pain, and joint disability score. Interestingly, the number of steroid hormone receptor positive cells decreased markedly (p<0.05 for all four receptors). The decrease in estrogen receptor alpha positive cells correlated significantly with the improvement in VAS pain and joint disability score. The number of glucocorticoid-, androgen-, and estrogen alpha and beta receptor positive cells before injection did not predict the effect of this treatment. Conclusions: Intra-articular glucocorticoid injections followed by bed rest for persisting arthritis are clinically effective and significantly decrease the number of steroid hormone receptor positive cells in ST. The relevance of the latter needs further study. Disclosure of Interest: None Declared